RETROFIT SUSTENTÁVEL: ESTUDO DE CASO EM EDIFICAÇÃO RESIDENCIAL - Sartori, Thais; Calmon, João Luiz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The energy industry produces many environmental impacts, related to the emission of greenhouse gases, water pollution or changes on the ecosystems. The architecture, engineering and construction industry represents around 30% to 40% of energy consumption in the world. One of the ways The study presented in this article is part of a broader research that aims to develop retrofit guidelines for different typologies of residential buildings in a neighborhood located in Vitória (ES). Therefore, this article compares efficiency levels in one of the identified typologies after the implementation of different green retrofit alternatives. The analysis was done through simulations in EnergyPlus software. The envelope parameters established by the Technical Regulation for Energy Efficiency levels in Residencial Buildings (RTQ-R) for the city of Vitória. The results show that the interventions made in the existing building were effective on reducing the hourly operative temperature (TO) and the amount of Degree-hours for cooling (GHR). The simulation software is a dynamic tool for decision making, and to provide effective parameter for the public services in order to establish constructive codes.